Are Applied Growth Factors Able to Mimic the Positive Effects of Mesenchymal Stem Cells on the Regeneration of Meniscus in the Avascular Zone?. (31st August 2014) - Zellner, Johannes; Taeger, Christian Dirk; Schaffer, Markus; Roldan, J. Camilo; Loibl, Markus; Mueller, Michael B.; Berner, Arne; Krutsch, Werner; Huber, Michaela K. I.; Kujat, Richard; Nerlich, Michael; Angele, Peter
Abstract : Meniscal lesions in the avascular zone are still a problem in traumatology. Tissue Engineering approaches with mesenchymal stem cells (MSCs) showed successful regeneration of meniscal defects in the avascular zone. However, in daily clinical practice, a single stage regenerative treatment would be preferable for meniscus injuries. In particular, clinically applicable bioactive substances or isolated growth factors like platelet-rich plasma (PRP) or bone morphogenic protein 7 (BMP7) are in the focus of interest. In this study, the effects of PRP and BMP7 on the regeneration of avascular meniscal defects were evaluated. In vitro analysis showed that PRP secretes multiple growth factors over a period of 8 days. BMP7 enhances the collagen II deposition in an aggregate culture model of MSCs. However applied to meniscal defects PRP or BMP7 in combination with a hyaluronan collagen composite matrix failed to significantly improve meniscus healing in the avascular zone in a rabbit model after 3 months. Further information of the repair mechanism at the defect site is needed to develop special release systems or carriers for the appropriate application of growth factors to support biological augmentation of meniscus regeneration.